Beispiel Nr: 06
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ -9x^3+25x =0\\ \\ \textbf{Rechnung:} \\ x(-9x^2+25)=0 \Rightarrow x=0 \quad \vee \quad-9x^2+25=0\\ -9x^2+25 =0 \qquad /-25 \\ -9x^2= -25 \qquad /:\left(-9\right) \\ x^2=\displaystyle\frac{-25}{-9} \\ x=\pm\sqrt{2\frac{7}{9}} \\ x_1=1\frac{2}{3} \qquad x_2=-1\frac{2}{3} \\ \underline{x_1=-1\frac{2}{3}; \quad1\text{-fache Nullstelle}} \\\underline{x_2=0; \quad1\text{-fache Nullstelle}} \\\underline{x_3=1\frac{2}{3}; \quad1\text{-fache Nullstelle}} \\$